A study managing the civil engineering risk focusing on risk reduction, risk financing and risk sharing / Mohd Syahmi Ahmad Sanusi - Ahmad Sanusi, Mohd Syahmi (Faculty of Business and Management, 2010)
Civil Engineering Risk is a consequences of unfavorable condition towards the Civil Engineering Structure such as tunnel, bridge, dam, road, canal and stadium by which the condition of collapse, destroyed by fire and damage by the other perils such as landslide, subsidence, flood, impact damage and impact from the aircraft. The issue is how to manage this risk with the focus on the risk reduction, risk financing and risk sharing. The objective of this study is to explore the civil engineering risk through the nature of the risk which is reviewing it through the fundamental knowledge of insurance and risk which is learning by the researcher during the studies in the UiTM with the comparison from what the researcher learned from the industrial training. Then, to explain what will happen to the industry if the civil engineering risk is not controlled by the industry including the construction and insurance industry. Then, to find out the most suitable measurement that could be taken by the insured or the owner through the Risk Management Techniques. In order to analysing the civil engineering risk, the researcher has been searching the data through the primary and secondary data sources. Primary data was obtained from the interview with the manager of Alloy Insurance Brokers and the secondary data has been obtained from the policies, statistic, internet and new paper. During the study in the Alloy Insurance Brokers, the researcher has found that the brokers in the Alloy are doing the risk management process according to the Bank Negara Malaysia procedures. But, the insured are not taking the process accordingly as were told and advised by the brokers. They have skipped some of the process that making the process vulnerable to the risk exposure.